Age Differences in the Structured Assessment of Violence Risk in Youth (SAVRY). Issue 3 (2nd July 2016) - Childs, Kristina K.; Frick, Paul J.
ABSTRACT: This study examined age differences in (1) the latent structure of the SAVRY, (2) the correspondence among structured professional judgments of risk and an empirically-derived measure, and (3) the SAVRY's predictive validity for probation outcomes. The sample consisted of 177 juveniles placed on probation. Analyses were conducted on two separate age groups: ages 13–15 and 16–18. We found that the SAVRY measured "risk" similarly across age (i.e., invariant latent structures) and that structured judgments of risk corresponded with the empirically-derived measure across both age groups. However, findings regarding the predictive validity of the SAVRY for probation outcomes were mixed. These findings provide strong support for the measurement and construct validity of the SAVRY across age and highlight the need for additional research on age differences in the strength of its predictive validity.